A hazard-based duration model to quantify the impact of connected driving environment on safety during mandatory lane-changing. (September 2019) - Ali, Yasir; Haque, Md. Mazharul; Zheng, Zuduo; Washington, Simon; Yildirimoglu, Mehmet
Highlights: Examined the effects of connected driving environment on safety during mandatory lane-changing manoeuvres. Analysed driving performance and associated safety surrogates during mandatory lane-changing manoeuvres. Developed a hazard-based duration model for minimum gap time during lane-changing. The connected driving environment improves safety during mandatory lane-changing manoeuvres. Abstract: Lane-changing is among the more risky of manoeuvres required of drivers, as it requires matching the speed of nearby vehicles, identifying a suitable gap in traffic, ensuring that a driver's own movements are recognised by others, and a capable execution. The highly anticipated, future connected vehicle environment (CVE) is expected to reduce associated crash risk of lane-changing by providing driving aids, which utilise surrounding traffic information. The impact of CVE driving on safety during mandatory lane-changing, however, is unknown due to the novelty of the CVE and consequent scarcity of the data. As such, this study examines the effects of the CVE on safety during mandatory lane-changing manoeuvres. Seventy-eight participants performed mandatory lane-changing manoeuvres in a driving simulator experiment in the CARRS-Q Advanced Driving Simulator. The randomised driving conditions included baseline driving (without driving aids), CVE driving with perfect communication (on-time supply of driving aids), and CVE driving with communication delay (delayed supply of driving aids). The minimum gap time, which is a surrogate measure of safety representing time-to-collision, between the interacting vehicles during the mandatory lane-changing was modelled using a parametric accelerated failure time (AFT) hazard-based duration model. A gamma frailty specification was used to capture structured heterogeneity arising from the repeated measures design of the experiment. The AFT model reveals that the gap time during mandatory lane-changing manoeuvres is longer during CVE driving with perfect communication compared to both the baseline and CVE driving with communication delay scenarios. The gap times for young (18–26 years) and male drivers are shorter in the traditional driving environment, but longer during CVE driving with perfect communication. Overall, CVE driving assists drivers by increasing the safety and efficiency of mandatory lane-changing tasks.